Competitive Environment Analysis in Global Retail Companies Operation Strategy: A Data Envelopment Analysis (DEA) Based Approach - Zainal Putra; Muzakir Muzakir (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This research aims to find out the most competitive retail company operating in current global market based on the perspective of efficiency. A well-performed company is the company that is efficient in its operations. By using Data Envelopment Analysis (DEA) approach, this research differs from prior research because we used multivariable inputs, namely: asset, operational expense and the number of employees. The output variables used in this research are: total revenue, net profit, return on equity (ROE), return on assets (ROA), return on investment (ROI), dividend yield ratio and asset turnover ratio. The analysis results shows that six retail companies are “efficient” in its operation (efficiency score of 1.00), namely: Carrefour, Costco, Kroger Company, Home Depot Inc, JD.com Inc Adr and Alibaba Group Holdings Ltd ADR. Therefore, these companies are considered the most competitive in its operation strategy in the current global market, whereas there are four retail companies falls into category of “inefficient” (efficiency score < 1.00), namely: Walmart, Amazon.com Inc, Tesco PLC and Walgreens Boots Alliance Inc.